Pendidikan Diniyah Formal (PDF) Meningkatkan Mutu Pendidikan Dayah Tradisional di Aceh - Teuku Zulkhairi (Badan Litbang dan Diklat Kementerian Agama RI, 2021)
AbstractThis study discusses the role of the Formal Diniyah Education program in improving the quality of traditional dayah education in Aceh. The study using a qualitative approach. The data were obtained through observation, documentation,Â and semi-structured interviewÂ with Diniyah Institutionâ€™s managers in Dayah Babussalam. The data collected were analyzed descriptively. The results showed that the presence of the Formal Diniyah Education program was a solution for Dayah Babussalam to improve the quality of her education. In practice, the presence of the Formal Diniyah Education program makes the existing traditional curriculum more developed. In addition, with the Imtiá¸¥an Waá¹oni (IW) examination, the quality of students also increases. Likewise, the presence of the Formal Diniyah Education program has also made modern education management integrated with Dayah Babussalam. The motivation of students to study in the dayah is also increasing where the Formal Diniyah Education diploma is very effective in